Genetic diversity and pedigree assignment in tetraploid Pacific oysters (Crassostrea gigas) - Miller, PA; Elliott, NG; Rene Vaillancourt; Kube, PD; Anthony Koutoulis (2014)
Tetraploid Pacific oysters ( Crassostrea gigas ) are commonly used within aquaculture to generate predominantly sterile triploids for commercial use. Unlike triploids, tetraploids are fertile and can be spawned with each other to maintain a commercial breeding population. The impacts this hatchery perpetuation has on the genetic diversity of the tetraploid population and subsequent commercial triploid product are currently unknown. This study determines the diversity (number of alleles and heterozygosity), pedigree assignment and effective population size over two generations of tetraploid production. A significant drop in diversity was observed over two successive generations of tetraploid oysters spawned in 2008 and in 2011, likely due to different numbers of broodstock used. Similar to diploids, pedigree assignment in tetraploids showed unequal parental contributions and an effective population size smaller than the census population, thus the potential for inbreeding to occur in the future is high.